2016
DOI: 10.1007/s11356-016-6216-1
|View full text |Cite
|
Sign up to set email alerts
|

Airborne polybrominated diphenyl ethers (PBDEs), polybrominated dibenzo-p-dioxins/furans (PBDD/Fs), and dechlorane plus (DP) in concentrated vehicle parking areas

Abstract: This study investigated polybrominated diphenyl ethers (PBDEs), polybrominated dibenzo-p-dioxins/furans (PBDD/Fs), and dechlorane plus (DP) in air around three concentrated vehicle parking areas (underground, indoor, and outdoor) in a metropolitan of South China. The parking areas showed higher concentrations of PBDEs, PBDD/Fs, and DP than their adjacent urban area or distinct congener/isomer profiles, which indicate their local emission sources. The highest PBDE and DP concentrations were found in the outdoor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 44 publications
0
2
2
Order By: Relevance
“…Both indoor and outdoor levels of PBDEs in the present study were higher than those in Taiwanese home environments (Σ 14 PBDEs: 81.1 and 13.1 pg m -3 in indoor and outdoor air, respectively) (Shy et al, 2015) and ambient air in the rural area of Pingtung (Σ 14 PBDEs: 15.9 pg m -3 ) (Chao et al, 2014c). As compared with other studies published from 2004 to 2016 and shown in Table 2, the mean level of PBDEs in the indoor air in the present study was lower than those in the vehicle parking areas in southern China (Li et al, 2016) and e-waste storage facilities in Thailand (Muenhor et al, 2010), but levels were still higher than those in the domestic environment (Wilford et al, 2004;Takigami et al, 2009;Shy et al, 2015;Ding et al, 2016). Our value in the outdoor air was only lower than those collected from vehicle parking areas (Li et al, 2016), and in the e-waste storage facilities (Muenhor et al, 2010), and a PRD community (Ding et al, 2016).…”
Section: Resultscontrasting
confidence: 59%
See 1 more Smart Citation
“…Both indoor and outdoor levels of PBDEs in the present study were higher than those in Taiwanese home environments (Σ 14 PBDEs: 81.1 and 13.1 pg m -3 in indoor and outdoor air, respectively) (Shy et al, 2015) and ambient air in the rural area of Pingtung (Σ 14 PBDEs: 15.9 pg m -3 ) (Chao et al, 2014c). As compared with other studies published from 2004 to 2016 and shown in Table 2, the mean level of PBDEs in the indoor air in the present study was lower than those in the vehicle parking areas in southern China (Li et al, 2016) and e-waste storage facilities in Thailand (Muenhor et al, 2010), but levels were still higher than those in the domestic environment (Wilford et al, 2004;Takigami et al, 2009;Shy et al, 2015;Ding et al, 2016). Our value in the outdoor air was only lower than those collected from vehicle parking areas (Li et al, 2016), and in the e-waste storage facilities (Muenhor et al, 2010), and a PRD community (Ding et al, 2016).…”
Section: Resultscontrasting
confidence: 59%
“…As compared with other studies published from 2004 to 2016 and shown in Table 2, the mean level of PBDEs in the indoor air in the present study was lower than those in the vehicle parking areas in southern China (Li et al, 2016) and e-waste storage facilities in Thailand (Muenhor et al, 2010), but levels were still higher than those in the domestic environment (Wilford et al, 2004;Takigami et al, 2009;Shy et al, 2015;Ding et al, 2016). Our value in the outdoor air was only lower than those collected from vehicle parking areas (Li et al, 2016), and in the e-waste storage facilities (Muenhor et al, 2010), and a PRD community (Ding et al, 2016). In comparison with various indoor environments Thuresson et al, 2012;Newton et al, 2015;Shy et al, 2015), indoor air levels of PBDEs in the present study were lower than those in offices, day care centers, and cars, but higher than those in homes and apartments.…”
Section: Resultscontrasting
confidence: 53%
“…DP is a highly chlorinated flame retardant which is used in coating wires/cables, plastic roofing and textiles [47][48][49]. It is released into the environment via e-waste recycling practices, during manufacturing as well as from use of products containing DP [50,51].…”
Section: Dechlorane Plus (Dp)mentioning
confidence: 99%
“…BDE-209 concentrations were significantly lower in children whose mother's reported regularly using a sunshade beneath the front windscreen to keep the car cooler when the weather is hot, which is a common practice in Australia. PBDE concentrations in cars have previously been found to be associated with temperature and outdoor parking, which suggests that sunshade use may reduce airborne or dust BDE-209 concentrations in cars (369,370). Previous combined biomonitoringenvironmental monitoring studies have shown PBDE concentrations in dust from cars correlates with concentrations of PBDEs in their owner's serum (221,371).…”
Section: Concentrations In Faeces and Predicted Concentrations In Serummentioning
confidence: 99%